A Perspective on Perovskite Solar Cells: Emergence, Progress, and Commercialization - Zhang, Pengyu; Li, Menglin; Chen, Wen-Cheng (Frontiers in Chemistry, 2022)
With rapid progress in the past decades, solar cells using metal halide perovskites as the light absorbers have become a potential candidate for photovoltaic technology with high efficiency. Compared with crystalline silicon photovoltaics, perovskite solar cells (PSCs) exhibit more advantages due to low-cost materials, ease of fabrication, and flexibility. In this perspective, we briefly review the development of PSCs from discovery to laboratory research to industrial progress. Then, we discuss the merits and challenges of perovskite-based photovoltaic technology with crystalline silicon solar cells as a comparison. Although, the production of PSCs promises lower manufacture cost, scale-up solution process, and good reproducibility, operational stability and toxic lead needs to be addressed in the future. Finally, we provide some perspectives on the future commercialization of PSCs in the marketplace. It is shown that PSCs can be more promising in low-cost modules and tandem configurations.